2015
DOI: 10.1016/j.aap.2015.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Mistakes or deliberate violations? A study into the origins of rule breaking at pedestrian train crossings

Abstract: Train pedestrian collisions are the most likely to result in severe injuries and fatalities when compared to other types of rail crossing accidents. However, there is currently scant research that has examined the origins of pedestrians' rule breaking at level crossings. As a result, this study examined the origins of pedestrians' rule breaking behaviour at crossings, with particular emphasis directed towards examining the factors associated with making errors versus deliberation violations. A total of 636 ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 16 publications
2
16
0
Order By: Relevance
“…The increased number of accidents between 2003 and 2011 in Australia at LCs which involved pedestrians have been studied by Stefanova et al [17]. The finding of Freeman and Rakotonirainy [18] show that pedestrians are more likely to deliberately violate traffic rules rather than make errors and suggested that there is a need to develop the injured prevention education schemes that will help to reduce the number of pedestrians involved in accidents at LCs. The low probability of pedestrians violating traffic rules at LCs to be apprehended can be prone to repeat the dangerous habit.…”
Section: Level Crossing Accidents and Types Of Users Involvedmentioning
confidence: 99%
“…The increased number of accidents between 2003 and 2011 in Australia at LCs which involved pedestrians have been studied by Stefanova et al [17]. The finding of Freeman and Rakotonirainy [18] show that pedestrians are more likely to deliberately violate traffic rules rather than make errors and suggested that there is a need to develop the injured prevention education schemes that will help to reduce the number of pedestrians involved in accidents at LCs. The low probability of pedestrians violating traffic rules at LCs to be apprehended can be prone to repeat the dangerous habit.…”
Section: Level Crossing Accidents and Types Of Users Involvedmentioning
confidence: 99%
“…Deviation from established safe diving practices has also previously been found associated with recreational diving mortality [4,5], morbidity and near-miss incidents [6,7]. Previous researchers in non-diving settings have noted that many unsafe deviations appear to be intentional choices, later thought associated with fatalities [8,9]. Lagache [10] found 87% of fatalities in the 1989 Ontario Underwater Council reports had such deviations, with 86% contributing to the chain of events leading to death.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that these are likely ineffective measures, considering that 60% of drivers will ignore traffic signal direction and circumvent warning systems even when a train is visible (Larue, Naweed, & Rodwell, 2018). Users are also more prone to deliberately, as opposed to accidentally, break crossing rules (24.52% vs 3.46%; Freeman & Rakotonirainy, 2015). This is not an issue of fundamental safety, but of a system design that is likely incompatible with user needs, behaviors, and perceptions.…”
Section: Introductionmentioning
confidence: 99%